2018
DOI: 10.1021/acs.analchem.8b04187
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveal That Octocrylene Accumulates in Pocillopora damicornis Tissues as Fatty Acid Conjugates and Triggers Coral Cell Mitochondrial Dysfunction

Abstract: Octocrylene (OC) is an ingredient used in many sunscreens and cosmetics worldwide. Our group evaluated the toxicity of OC in corals. Adult Pocillopora damicornis coral was treated with OC at concentrations of 5, 50, 300 and 1000 µg/L. Most polyps were closed at concentrations of 300 µg/L and higher. Further, metabolomic profiling provided crucial information regarding OC accumulation in coral tissues and OC toxicity. First, we demonstrated that OC was transformed into fatty acid conjugates via oxidation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 28 publications
4
87
0
Order By: Relevance
“…We also observed a concentration-dependent increase in mortality of Artemia with respect to the control. This is congruent with the toxicity observed, at lower concentration, on coral (50 µg/L) [23], urchin, mussel and algae (40-80 µg/L) [19]. OC also affects the developmental process in zebrafish [37].…”
Section: Effects On Artemia Salina Mortalitysupporting
confidence: 86%
See 1 more Smart Citation
“…We also observed a concentration-dependent increase in mortality of Artemia with respect to the control. This is congruent with the toxicity observed, at lower concentration, on coral (50 µg/L) [23], urchin, mussel and algae (40-80 µg/L) [19]. OC also affects the developmental process in zebrafish [37].…”
Section: Effects On Artemia Salina Mortalitysupporting
confidence: 86%
“…Several studies have demonstrated that some of these compounds can disrupt survival [12][13][14]. behavior [15,16], growth [14,17,18], development [19,20], metabolism [21][22][23], gene expression [24,25] and reproduction [15,26,27] in various species. It should be noted that most toxicological studies on organic UV filters were conducted on BP3, EMC and 4-MBC [7].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, it has been suggested that studying the coral polyps, which serves as model organisms for reef corals, is a more plausible way to acquire the necessary physiological information to understand the biological behaviors of reef corals [11][12][13][14][15] . However, it still remains a challenge to collect and culture single coral polyps in vitro 16 .…”
mentioning
confidence: 99%
“…In the current study, P. damicornis nubbins were exposed to ES for 7 days at concentrations of 5, 50, 300 and 1000 µg/L. As with OC previously, the extracts prepared from the coral nubbins exposed to ES were analyzed by UHPLC-ESI + -HRMS 2 and compared with control experiment 7 .…”
mentioning
confidence: 99%
“…Interestingly, the differential analysis www.nature.com/scientificreports www.nature.com/scientificreports/ showed that all these compounds were significantly upregulated when the coral was exposed to ES at concentrations ranging from 50 to 1000 µg/L. It turned out that the concentration of 14 also increased upon exposition to OC 7 , and at this point, it was clearly necessary to determine unambiguously the structure of compound 14. Extensive fractionation allowed for the isolation of 14 in its pure form, which was ultimately identified by NMR as the known steroid (3β,5α,8α)-5, 8-epidioxy-ergosta-6,24(28)-dien-3-ol.…”
mentioning
confidence: 99%